Potensi Sumberdaya Udang Penaeid di Perairan Kepulauan Aru Bagian Timur Sub Wilayah Aru dan Sekitarnya - Franklyn Hoek; Silvester Simau; Muhfizar Muhfizar; Amir Suruwaky,; M Ali Ulat; Arhandy Arfah (Jurnal Airaha, 2015)
The utilization of the resources of shrimp penaeid in the eastern part of the archipelagic waters Aru and surrounding sub-region III, to estimate the abundance of shrimp by using the swept area method. The aim of research to determine the composition of species caught by shrimp trawlers using a double rig, Comparative production of penaeid shrimp catch in 2014 and in 2012. Potential sustainable and penaeid shrimp with Swept area method. Results Composition Penaeid Shrimp Catch in archipelagic waters Aru and surrounding sub-region (III). There are 9 types of penaeid shrimp with the amount of catches of 17 988 kg and is the most dominant type of Green Tiger Prawn (Penaeus semisulcatus), while the lowest amount was kind Banana Prawn (Penaeus merguensis). The results of a comparative test with Chi Square (χ2) turns Ho rejected and Ha accepted, wherein χ2 count 7.40 is greater than χ2 tables 0.05 (3.84) and χ2 tables 0.01 (6.63), this means that there are differences in yield catches in 2012 And in 2014 was very significant. There is a decline in production is very significant from 2012 until 2014. The potential outcome in the waters of the sub region Aru Islands and surrounding waters -III which covers 13,000 km2, where willingness stock (B) 579.58 tons, sustainable potential (MSY) amounted to 576.58 tons / year while the Total Allowable Catch (TAC) amounted to 463.67 tons / year.